Evaluation of food provision and nutrition support at the London 2012 Olympic Games: The opinion of sports nutrition experts - Pelly, F. E.; Meyer, N. L.; Pearce, J.; Burkhart, S. J.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The aim of this study was to evaluate the food provision and nutrition support at the London 2012 Olympic (OG) and Paralympic Games (PG) from the perspective of sports nutrition experts attending the event. Participants (n = 15) were asked to complete an online survey and rate on a Likert scale menu qualities, food safety, sustainability practices, nutrition labeling, and provision for cultural needs, dietary regimes and specific situations. Open-ended responses were incorporated to explore expert opinion and areas for improvement. Participants rated their overall experience of the food provision as 7.6 out of 10 (range 5 to 10), with the majority (n = 11) rating it greater than 7. The variety, accessibility, presentation, temperature, and freshness of menu items rated as average to good. A below average rating was received for recovery food and beverages, provision of food for traveling to other venues, taking suitable snacks out of the dining hall and provision of food at other venues. However, the variety and accessibility of choices for Ramadan, and provision of post-competition food were rated highly. A number of comments were received about the lack of gluten free and lower energy/fat items. The inclusion of allergens on nutrition labeling was considered more important than nutrient content. While dietetic review of the menu in advance of the OG and PG is clearly a valuable process that has resulted in improvements in the food supply, there are still areas that need to be addressed that are currently not implemented during the event.